Evaluation Of KMP Tariff Calculation. Siginjai On The Jepara – Karimunjawa Crossing Based On The Minister Of Transportation Regulation No. Pm. 66 Of 2019 Concerning The Mechanism Of Determining And Formulating The Calculation Of Ferry Transport Fares - Mangatur T Brenhard; Santoso Santoso; Sri Kartini; Muhammad Afif (IWJ : Inland Waterways Journal, 2021)
Jepara Ferry Port is a port located in Jepara District, Jepara Regency which serves the Jepara - Karimunjawa route. In terms of needs, tariffs are very influential on the level of transportation services, especially in the fulfillment of public services. However, the tariffs that apply on the Jepara - Karimunjawa route are now tariffs based on the old regulations. In addition, there is also a change in the Production Unit (SUP) for the type of vehicle class in accordance with Attachment I, Regulation of the Minister of Transportation Number 66 of 2019 concerning Mechanisms for Determining and Formulating the Calculation of Ferry Transport Tariffs. The aims of this study are as follows: 1) Knowing the operational costs of ships (BOK) on the Jepara - Karimunjawa route based on the Regulation of the Minister of Transportation Number PM. 66 of 2019. 2) Knowing the calculation of ferry transportation fares on the Jepara - Karimunjawa route based on the Regulation of the Minister of Transportation Number PM. 66 of 2019. The research methodology used is direct observation in the field (field research), interviews (interviews), literature/documentation (literature) and institutional. Then to analyze this, it is guided by Ministerial Regulation Number 66 of 2019 concerning the Mechanism of Determining and Formulating the Calculation of Ferry Transport Tariffs. The analysis used is load factor analysis, ship operational cost analysis and unit tariff analysis. The results of this study are 1) The tariffs set are not in accordance with the results obtained by the author based on the calculation of ship operating costs (BOK) which refers to the Regulation of the Minister of Transportation Number PM. 66 of 2019. 2) That the tariff on the Jepara - Karimunjawa route in Central Java Province is not relevant to current conditions, due to the Change of Production Units (SUP) in the management system at PT. ASDP Indonesia Ferry (Persero) Jepara Branch. 3) Evaluation of Tariffs on the Jepara - Karimunjawa Route in Central Java Province Has Changed in accordance with the following provisions a) That the Increase in Tariff Units Now Follows Ministerial Regulation Number 66 of 2019 which states that the current production units have increased from the previous.